The “new dentistry” in the “new normal” - Perona-Miguel de Priego, Guido Alberto (2021)
The purpose of this work is to provide dentist surgeons who care for children and adolescents during and after the COVID-19 pandemic, suggestions for care with minimally invasive treatment alternatives to reduce the risk of cross-viral infection and offering a safer clinical environment.